Software used in emergency medical services - Procházka, Jan; Bruthans, Jan (Casopis lekaru ceskych, 2021)
Management of documentation in emergency medical services poses specific challenges due to its mode of operation. Electronic aids are already being used in this field. This article identifies four key systems: documentation management software, software for diagnostic devices, software for county emergency dispatches and navigational software. Each county emergency services provider in the Czech Republic is now equipped with all aforementioned systems. Most of these providers are also able to perform remote ECG consultations.
Keywords: Emergencies; emergency medical services; urgentní zdravotnické služby; Česká republika; Czech Republic; Instrumentation; Telemedicine; lidé; Humans; Software; information systems; equipment; telemedicine; náhlé příhody; Emergency Medical Services; software